AB0554 Nailfold Capillaroscopic Findings in Systemic Autoimmunes Diseases. (9th June 2015) - Movasat, A.; Turriόn, A.; Moruno, H.; Bohorquez, C.; Pérez, A.; Sanchez, A.; Cuende, E.; Albarran, F.; Romero, M.L.; Ruiz, L.; Alvarez Mon, M.
Abstract : Background: Nailfold capillaroscopy is a simple, safe, low cost and non-invasive screenig test and together with the study of autoantibodies, is useful in the diagnosis of systemic sclerosis (SSc). It demonstrates certain specific patterns which are characterized by the presence of dilated capillaries, haemorrhages and avascular areas. Other autoimmune rheumatic diseases (ARD) do not have a specific pattern, but certain alterations in the morphology of the capillaries such as increased tortuosity have been described in SLE. In other diseases such as mixed connective tissue disease (MCTD), inflammatory myopathies and overlap syndromes, findings may be different to the pathological findings consistent with scleroderma pattern. Objectives: Description of nailfold capillaroscopic findings in different ARD Methods: All patients sent to the our Department to perform a capillaroscopy between January 2012 and December 2014 were included in the study. Capillaroscopy was performed in 8 fingers, and always by the same observer. The following findings were considered as "scleroderma pattern": Local or global capillary loss (>20%), Haemorrhages: two or more in at least two fingers and Enlarged capillaries: two or more capillary with double caliber or more in at least two fingers. Abundant evidence of tortuosity (>20%) as ringlets tangles and no evidence of disorders described above, was considered nonspecific, tortuous pattern or suspect ARD. Statistical analysis was performed with SPSS 19.0 program. Results: Capillaroscopy was performed in 211 patients, 24 males (11%) and 187 (88.6%) women, with a mean age of 44 years (±16). 22 patients (10.5%) had a diagnosis of SSc, 6 patients (2.8%) of SLE, other 6 (2.8%) of Sjögren's syndrome, 6 (2.8%) of MCTD, 3 (1.4%) of inflammatory myopathy and 1 (0.5%) of overlap syndrome. 14 patients (6.6%) had positive ANA and Raynaud without another data suggestive of ARD, 53 patinents with primary Raynaud's syndrome (25.1%) and 59 patients (27.9%) with a miscellany of other diseases such as antiphospholipid syndrome, vasculitis, fibromyalgia and psoriatic arthritis. Also, 26 patients (12.3%) were sent for performing capillaroscopy for suspected SSc and 13 patients (6.2%) presented with only positive anti-centromere. Capillaroscopy was normal in 151 patients, while in 41 patients scleroderma pattern was observed and in 15 patients nonspecific pattern suggestive of ARD was seen. Capillaroscopic findings: in each of the 22 patients diagnosed with SSc, 20 patients had scleroderma pattern. Of the 6 patients with SLE, capillaroscopy was normal in 4 patients, while one patient had abundant tortuosity. Likewise, the 6 patients with Sjögren's syndrome, only one patient had a nonspecific pattern suggestive of ARD. Of the 6 patients with MCTD, three had normal capillaroscopy, two had a scleroderma pattern and one had tortuous pattern. The only patient with overlap (myopathy-scleroderma) had a pathological capillaroscopy with scleroderma pattern. Conclusions: Our study demonstrates that the evidence of scleroderma pattern is very specific of SSc. However, in certain diseases such as MCTD, overlap syndromes and inflammatory myopathies, we can also see this pattern. In other ARD, capillaroscopy is usually normal or may show some nonspecific changes. Disclosure of Interest: None declared